Students' mathematical critical thinking through the conceptual change approach - Maghfiroh, Fitria; Dasari, Dadan (Jurnal Riset Pendidikan Matematika, 2023)
Critical thinking ability is one of the higher order thinking skills. Students who have high critical thinking skills are expected to have the ability to analyze problems properly and precisely. The purpose of the present study was to find out the differences in students' mathematical critical thinking skills who received learning using the conceptual change approach and those who received conventional learning, namely the scientific approach. This study was conducted at a junior high school in South Tangerang City, Banten Province. The research method used was a quasi-experimental research design with a post test only control design. The research sample consisted of 70 students consisting of 37 students in the experiment group and 33 students in the control group selected by a cluster random sampling technique. Results indicate that students' mathematical critical thinking skills who learned with the conceptual change approach are higher than those of students who learned by the scientific approach. The critical thinking skills of students who received learning by the conceptual change approach were 72.64%, on the indicator of analyzing arguments, 67.23%, on the indicator of  making conclusions,  84.46%, on evaluating, and 61.85%  on solving problems